The Invisible Universe: The Story of Radio Astronomy - Verschuur, Gerrit (Springer, 2016)
Hidden from human view, accessible only to sensitive receivers attached to huge radio telescopes, the invisible universe beyond our senses continues to fascinate and intrigue our imaginations. Closer to home, in the Milky Way galaxy, radio astronomers listen patiently to the ticking of pulsars that tell of star death and states of matter of awesome densities. All of this happens out there in the universe hidden from our eyes, even when aided by the Hubble Space Telescope.